Traditional Khmer Medicine and its role in wildlife use in modern-day Cambodia - Thona Lim; Elizabeth Oneita Davis; Brian Crudge; Vichet Roth; Jenny Anne Glikman (BMC, 2022)
Abstract Individuals across Cambodia depend on the use of natural products in Traditional Khmer Medicine (TKM), a traditional medicine system in Cambodia that has been practiced for hundreds of years. Cambodia is rich in fauna and flora species, many of which have been, and continue to be, traded domestically for traditional medicine use. Combined with other known exploitative practices, such as snaring for wild meat consumption and international trade in wildlife, domestic trade in wildlife medicine threatens populations of regional conservation importance. Here, we provide an updated understanding about how TKM is practiced in modern times; how TKM practices are transmitted and adapted; and roles of wildlife part remedies in TKM historically and presently. We conducted semi-structured interviews with TKM practitioners in Stung Treng, Mondulkiri Province, and at the National Center for Traditional Medicine in Phnom Penh, the capital of Cambodia. TKM is generally practiced in the private sector and is mostly informal, without enrollment in any academic training. TKM practitioner roles commonly involve collecting, preparing, selling, and advising on medicine, rather than providing direct treatment. Over half of the interviewed TKM practitioners (57.6%) were still prescribing wildlife parts as medicine over the past 5 years, with 28 species of wild animals reported. Lorises and porcupine were the wildlife products cited as being in highest demand in TKM, primarily prescribed for women's illnesses such as post-partum fatigue (Toas and Sawsaye kchey). However, the supply of wildlife products sourced from the wild was reported to have dropped in the 5 years prior to the survey, which represents an opportunity to reduce prescription of threatened wildlife. We suggest that our results be used to inform tailored demand reduction interventions designed to encourage greater reliance on biomedicine and non-threatened plants, particularly in rural areas where use of biomedicine may still be limited.